Cesar Moro and his translators - Nájar, Jorge (2017)
While outlining some of the personality of the poet profiles, an approach to the most important milestones of this poetry from the first moments until the final texts is suggested. In the midst of all this, the role played by different translators who undertake the work of Cesar Moro is crucial. The characteristics of the two major aditions of his complete poetry made one by Unesco and the other by the Academia Peruana de la Lengua (Peruvian Academy of the language- as reference in English) is also discussed.